EFFECTIVE OPPOSITION AND DEMOCRATIC CONSOLIDATION IN NIGERIA (2007-2015) - Udeuhele, Godwin Ikechukwu (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Experience predisposes us to accept that in Africa and particularly Nigeria, opposition political parties are easily suppressed upon and factionalized via the political antics of the ruling party and its stooges within such opposition political party and thus that seemingly diminishes its internal cohesion and efficacy. Thus this study raises concerns on the ability of Africa’s opposition parties playing out their roles effectively in the democratic enterprise and overall political development of the countries within the continent. Over the decades this has remained a pipe dream, because myriads of questions persist pertaining to the substance, quality and effectiveness of opposition political party in Africa’s nascent democracies. The study adopted Marxist theory of post-colonial state, longitudinal research design, qualitative method of data enquiry and analysis. The study found out that Africa and Nigeria in particular is still at the nascent stage in her political process and most of the existing political parties in the continent are apparently bereft of clear ideologies, which places great burden on their ability to act as credible oppositions as well as a force in driving democratic sustainability and overall political development of their various countries. The study recommended that virile political institutions, ideologically driven political parties will in no small measure help to engender the consolidation of democratic governance. Leaders and operators of opposition parties should make dividends of good governance accessible to the masses by acting as watch dog in checkmating the activities of the party in government through effective, credible and proactive means